The Impact of Psychological Exercises in a Competitive Environment on Enhancing Mental Resilience and Endurance And development Some Types of Scoring in Futsal: Pengaruh Latihan Psikologis dalam Lingkungan Kompetitif terhadap Peningkatan Ketahanan Mental dan Daya Tahan Serta Pengembangan Beberapa Jenis Sistem Penilaian dalam Futsal - Ahmed Mahmoud Shakir (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Psychological factors play a crucial role in shaping athletic performance and competitive success in sports contexts. Specific Background: Among these factors, psychological endurance and self-talk are widely recognized as key elements that support athletes in maintaining focus and managing performance demands. Knowledge Gap: However, limited empirical studies have examined the relationship between psychological endurance and self-talk within specific athletic populations. Aims: This study aims to identify the relationship between psychological endurance and self-talk in sports performance. Results: The findings indicate a statistically significant relationship between psychological endurance and self-talk, suggesting that athletes with higher endurance levels demonstrate more effective use of self-directed cognitive strategies. Novelty: The study provides an integrated perspective on the interaction between psychological endurance and self-talk within a sports setting. Implications: These findings offer practical insights for coaches and athletes to incorporate psychological training strategies that support performance consistency and mental resilience. Keywords: Psychological Endurance, Self Talk, Sports Performance, Mental Training, Athlete Psychology Key Findings Highlights Higher mental resilience is associated with stronger use of cognitive regulation strategies Internal dialogue patterns relate to consistency in athletic execution Psychological preparation supports stability during competitive situations